A comparison of tibial and peroneal venous and HePTFE bypasses in diabetics with critical limb ischemia. Issue 2 (April 2017) - Hock, C.; Betz, T.; Töpel, I.; Bröckner, S.; Steinbauer, M.; Uhl, C.
Abstract: Objective: In this study we analyzed the outcome of tibial and peroneal venous and heparin-bonded expanded polytetrafluoroethylene (HePTFE) bypasses in diabetics with critical limb ischemia (CLI). We aimed to verify our hypothesis that HePTFE grafts will achieve acceptable 1-year patency and limb salvage results in patients who lack an adequate vein. Methods: We conducted a retrospective analysis for all diabetics who underwent tibial bypass surgery in our department between October 2007 and October 2012. The study includes 97 grafts. All these patients were not suited for an endovascular therapy. We used autologous veins in 56 cases (Vein-Group) and HePTFE grafts in 41 cases (HePTFE-Group). Study endpoints were primary and secondary patency, limb salvage, and survival at 2 years postoperatively. Results: Risk factors and indications were similar in both groups. The comparison between HePTFE- and Vein-Group showed significantly different patency rates. At 2 years, primary patency was 39.3% in HePTFE-Group vs. 78.5% in Vein-Group (P = .003) and secondary patency was 47.4% vs. 81.9% (P = .002). Limb salvage at 2 years was 79.3% vs. 87.4% (P = .073) and survival was 64.6% vs. 62.9% (P = .593) at the 2-year mark, with no significant differences. 30-days mortality, graft occlusion and major amputation rate showed no significant differences, either. Conclusions: This study shows that HePTFE bypasses are a viable option for diabetics undergoing tibial bypass surgery when no adequate vein is available.